Does somatic illness explain the association between common mental disorder and elevated mortality? Findings from extended follow-up of study members in the UK Health and Lifestyle Survey. Issue 7 (1st February 2012) - Batty, G David; Hamer, Mark; Der, Geoff
Abstract : Background: Common mental disorder (psychological distress) is associated with an increased risk of disease-specific mortality. Given that physical illness is related to both exposure and outcome, it may explain this relation through confounding or mediation. Methods: The authors used a 20-year follow-up of the UK Health and Lifestyle Survey (6127 men and women) in which common mental disorder was ascertained at baseline using the 30 item General Health Questionnaire and physical illness using a range of enquiries. Study members were an average of 45.2 years (SD 17.0) at study induction. Results: In age-adjusted analyses, a 1 SD increase in common mental disorder score was associated with an elevated risk of mortality outcomes coronary heart disease (CHD) in men (HR 1.11, 95% CI 0.96 to 1.27), CHD in women (1.33, 1.16 to 1.51); plus, in men and women combined, stroke (1.13, 0.96 to 1.30), respiratory disease (1.31, 1.15 to 1.48), lung cancer (1.11, 0.92 to 1.33), 'other' cancer (1.14, 1.03 to 1.26) and all causes (1.18, 1.12 to 1.23). Controlling for prior physical illness effectively eliminated the common mental disorder–mortality relation in all analyses with the exception of CHD in women. Conclusion: That physical illness largely explains the link between common mental disorder and mortality in the present cohort is compatible with either a confounding or mediation explanation.